Teacher Salary Differentials and Out-of-Field Teaching - Bettye MacPhail-Wilcox; Robert T. Williams (Educational Considerations, 1984)
The problems posed by recurrent and resistant salary problems in education will require fundamental reconsideration of school organizational, operational and administrative strategies.